Peningkatan Keterampilan dalam Menulis Anekdot Menggunakan Strategi Genius Learning pada Siswa Kelas X ATPH di SMK Negeri 3 Alasa - Fince Putra Jaya Zalukhu; Heking Trisman Harefa; Fiman Astrid Nan Dindah Gulo; Mei Siska Putri Mendrofa (Lembaga Intelektual Muda Maluku, 2024)
Writing skills are an important component of language learning; however, many students still experience difficulties in developing ideas and organizing their writing effectively. This study aimed to improve students’ anecdote writing skills through the implementation of the Genius Learning strategy. The research employed Classroom Action Research conducted in two cycles. The participants were 32 students of class X ATPH at SMK Negeri 3 Alasa, North Nias. Data were collected through observation, questionnaires, tests, and documentation. The data were analyzed using descriptive quantitative and qualitative approaches. The results of the study showed that students’ anecdote writing skills improved significantly after the implementation of the Genius Learning strategy. The average score increased from 64.53 in the pre-action stage to 75.58 in cycle I and further improved to 85.00 in cycle II. In addition, the learning process also showed positive changes in students’ participation, attention, and learning enthusiasm. The findings indicate that the Genius Learning strategy creates a more engaging and meaningful learning environment, which supports students in developing their writing skills. Therefore, the Genius Learning strategy can be considered an effective instructional strategy for improving students’ anecdote writing skills in Indonesian language learning